Facilitating Multiparty Dialog with Gaze, Gesture, and Speech - Bohus, Dan; Horvitz, Eric (2010)
We study how synchronized gaze, gesture and speech rendered by an embodied conversational agent can influence the flow of conversations in multiparty settings. We review a computational framework for turn taking that provides the foundation for tracking and communicating intentions to hold, release, or take control of the conversational floor. We then present details of the implementation of the approach in an embodied conversational agent and describe experiments with the system in a shared task setting. Finally, we discuss results showing how the verbal and non-verbal cues used by the avatar can shape the dynamics of multiparty conversation.